Increased risk of water quality deterioration under climate change in Ganga River - Santy, Sneha; Mujumdar, Pradeep; Bala, Govindasamy (Frontiers in Water, 2022)
The industrialized stretch of Kanpur is considered to be one of the most polluted stretches of the Ganga River, with untreated sewage, industrial discharge, and agricultural runoff. Risk assessment studies on water quality for future scenarios are limited for this stretch of the river. In this study, we assess the effect of climate change on water quality, the risk of eutrophication, and fish kill for the mid and end of the 21st century for this river stretch. The water quality parameters considered are dissolved oxygen (DO), biochemical oxygen demand (BOD), ammonia, nitrate, total nitrogen, organic-, inorganic- and total phosphorous, and faecal coliform. The risk of eutrophication and fish kill are quantified using simulated concentrations of nutrients and DO, respectively. Downscaled climate change projections for two climate change scenarios (RCP4.5 and RCP8.5) are used to drive a hydrological model coupled to a water quality simulation model. Our simulations indicate a potential deterioration of water quality in this stretch in the mid-21st century, with a potential increase in pollutant concentration by more than 50% due to climate change alone. However, a slight improvement is simulated by the end of the century relative to the mid-21st century which can be attributed to increased streamflow during low-flow periods due to increased summer mean precipitation. The risk of reduced dissolved oxygen and increased organic and nutrient pollution, and the risk of eutrophication and fish kill increase with warming due to the rise in the frequency of low-flow events and a reduction in streamflow during low-flow events. However, the risk of nitrate and microbial pollution is reduced because of an increased denitrification rate and pathogen decay rate with warming. The risk of eutrophication and fish kill is found to increase by 43.5% and 15% due to climate change alone by mid-21st century. Our findings could be helpful to planners in water resource management to take necessary actions to improve the water quality of the Ganga River in this century.